Factors that influence job satisfaction among employees at Petronas Gas Berhad / Adida Salwa Mohd Jamaludin - Mohd Jamaludin, Adida Salwa (Faculty of Business and Management, 2007)
Employees are one. of the company assets that are very important in order to make sure that the company operation can run smoothly. Therefore many companies believe that it is important to make sure that their employees are happy and satisfy with all the benefits and facilities while they are working. Job satisfaction is importance to an organization in terms of improving its efficiency, increasing productivity, maintaining employee relations, lowering absenteeism and turnover. The main objectives of this research are to identify the factors that influence employee job satisfaction among the employees of PETRONAS Gas Berhad and identify significant relationship between those factors with job satisfaction.